Infinitely many smooth nodal solutions for Orlicz Robin problems - Bahrouni, Anouar; Missaoui, Hlel; Radulescu, Vicentiu (Elsevier, 2023)
In this note, we study a Robin problem driven by the Orlicz g-Laplace operator. In particular, by using a regularity result and Kajikiya's theorem, we prove that the problem has a whole sequence of distinct smooth nodal solutions converging to the trivial one. The analysis is developed in the most general abstract setting that corresponds to Orlicz-Sobolev function spaces.

In this note, we study a Robin problem driven by the Orlicz g-Laplace operator. In particular, by using a regularity result and Kajikiya's theorem, we prove that the problem has a whole sequence of distinct smooth nodal solutions converging to the trivial one. The analysis is developed in the most general abstract setting that corresponds to Orlicz-Sobolev function spaces.
Infinitely many smooth nodal solutions for Orlicz Robin problems
Keywords: Nodal solutions; Orlicz-Sobolev spaces; Robin boundary value; Regularity; Nodal solutions; Orlicz-Sobolev spaces; Robin boundary value; Regularity